Development of the Future Specialist’s Basic Competence in the professional Education Conditions - Farida, Orazakynkyzy; Salima, Shalenova; Gulmira, Katpayva; Ardak, Kaliolla; Assel, Almabekova (International Journal of Psychosocial Rehabilitation, 2020)
This research paper reviews the significance of the professional education of the future specialists in terms of formation of their readiness to the activity. The reorientation of society to the market relations was required major changes in the system of vocational education. When employment, the employer is interested not store of theoretical knowledge of graduates of higher and secondary special educational institutions, but their preparedness to fulfillment of professional activities in this area. In connection with these requirements of employers and society in our country, were started the implementation of professional system of education. There has developed the innovative labor market in Kazakhstan. And it is necessary to review the traditional approaches in system of vocational education. However, the educational institutions cannot to shift to the new goals of specialists training yet. Together with this, given manuscript demonstrates the necessity of professional education in educational system of the Republic of Kazakhstan for enhancement the professional preparation of the specialists